Essential reporting items within a law enforcement recruit injury and physical performance database: A modified Delphi study - Myles C. Murphy; Simone Radavelli-Bagatini; Garth Allen; Nicolas H. Hart; Andrea B. Mosler (Elsevier, 2023)
Objective: Collate the perceptions and experience of relevant key stakeholders to develop reporting guidelines for epidemiological injury and physical performance data within law enforcement agencies recruit training programs. Design: An augmented Delphi consensus process. Methods: Initial item generation occurred via online, one-on-one, semi-structured interviews, and followed by one survey round. Items generated from interviews were categorised within three main categories: i) Demographic data, ii) Injury data, and iii) Physical performance data. Participants represented one-of-six target groups: Police officers; Police physical training staff; Police occupational health and safety staff; Elite sport high performance staff; Military high-performance staff; Physical activity injury epidemiologists. Results: A total of 15 representatives (53% women) from six stakeholder groups were included. Other than responses directly related to item generation, three main themes emerged from round one: i) recruits are not likely to report all data being requested truthfully, ii) data that is recorded must be acted upon, and iii) body fat assessments should not be included in this population with focus instead being placed on performance. Three separate reporting databases were generated. Conclusion: Our study established clear demographic, mental health/physical injury, and physical performance data to be collected in a law enforcement recruit training program for injury surveillance and performance monitoring. Furthermore, we identified several items that were classified as relevant, but unlikely to be reported truthfully. These items can help inform current practice and assist clinicians to determine the trustfulness of information received by patients when working within law enforcement environments.